PENERAPAN MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, DAN EXTENDING (CORE) BERBANTUAN MEDIA CANVA DALAM PEMBELAJARAN MENULIS POSTER PADA SISWA KELAS VI SEKOLAH DASAR DI KECAMATAN GANEAS KABUPATEN SUMEDANG TAHUN PELAJARAN 2025/2026 - Listiyanti Meira Mubarokah; E.Sulyati; Asep Saepurokhman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Poster writing is an essential skill for students, especially in today's visual era. Through poster creation, students are trained to think creatively, organize ideas, and convey messages effectively and engagingly. Poster writing skills are beneficial not only in learning contexts but also in everyday life. Based on field observations, students experience difficulty formulating ideas or concepts, lack attractive designs, and lack writing skills. This is due to the lack of variety in the learning models implemented by teachers. This study aims to describe the differences in poster writing learning outcomes between sixth-grade elementary school students in Ganeas District, Sumedang Regency, using the Connecting, Organizing, Reflecting, and Extending (CORE) model with the aid of Canva and those without the CORE model with the aid of Canva in the 2025/2026 academic year. Therefore, the instruments used were teaching modules and tests. The method used in this study was a quasi- experimental study with qualitative and quantitative analysis. Based on data analysis, the success rate of poster writing learning using the CORE model with the aid of Canva in the experimental class was categorized as high. This is evidenced by the results of the z test which shows that z count -0.36 is located within the interval -Z0.4900 S.d Z0.4900 or -2.33 < -0.36 < 2.33. The success rate of learning to write posters using image media in the control class is classified as low. This is evidenced by the results of the z test which shows that z count -2.14 is located outside the interval -Z0.4900 S.d Z0.4900 or -2.14 > -2.33. There is no significant difference in the ability to write posters between those using the CORE model assisted by Canva media and those using the conventional model. This is evidenced by the results of the t test calculation which shows t count = 1.24 which is smaller than t0.995 = 2.66 or 1.24 < 2.66. Thus, both models can be used in